Single visit endodontic and direct restoration of inadequate treated mandibular molar: case report: Perawatan saluran akar kunjungan tunggal dan restorasi direk pada gigi molar rahang bawah yang telah dirawat secara tidak adekuat: laporan kasus - Fadil Abdillah (Makassar Dental Journal PDGI Makassar, 2019)
Introduction: Single visit root canal treatment (RCT) versus the multiple visit RCT has been the subject of a long standing debate within the dentist. Some of the unresolved issues include differences in clinical outcomes, inadequate microbial control and pain. In other hand, patients have no time to come in many appointments. Case: A19-year-oldfemalepatientcamewithacomplaint of uncomfortable over her first left mandibular molar.There was composite restoration on occlusal aspect of the tooth with no mobility and swelling. Radiograph showed a fillingmaterialfromthetopofpulpchambertothefloor.Therewasnoradiolucencyappearencesintheperiapical. Patienthasnomedicalcompromised.Casemanagement:Theinitialprocedurewasisolationusingrubberdam. The access was opened while eliminated the filling material using endo access diamond bur. Determined working canallengthusingapexlocatorandconfirmedwithradiography.ThecleaningandshapingwasdonewithProtaper Next rotary files. The 2.5% sodium hypochlorite, 17% EDTA and 0.12% chlorhexidine being used for final irrigation. The three canals were obturated with guttapercha and resin-based sealer by single cone method. The endorestotreatmentwasfinishedwithdirectcompositerestoration.Conclusion:Singlevisitendodontic has been shown to be an effective treatment modality when compared with multiple visit therapy and it does not deviate from achieving the objectives of proper biomechanical preparation, debridement, shaping, disinfection and 3 dimensional obturation of root canal system and is more beneficial to the patient and dentist provided there is careful case selection and strict follow of standard endodontic protocols.